High-wear-resistance FeZr-ZTA micro powder coated ZTA ceramic reinforced high-chromium cast iron-based composite material as well as preparation and application thereof

Through the FeZr-ZTA micropowder coated ZTA ceramic particles surface activation treatment technology, the problem of poor bonding between the ceramic particles and high chromium cast iron is solved, the metallurgical interface is combined, and the wear resistance of the composite material is significantly improved.

CN119800210AActive Publication Date: 2025-04-11JINAN UNIVERSITY

Patent Information

Application Number
CN202510015191.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The interface bonding method of existing ceramic particle-enhanced high-chromium cast iron composite materials is mainly mechanical bonding, which is difficult to achieve metallurgical bonding, resulting in poor bonding between ceramic particles and high-chromium cast iron, affecting wear resistance.

Method used

Through the FeZr-ZTA micropowder coated ZTA ceramic particles surface activation treatment technology, the interface wetting of ceramic particles and high chromium cast iron matrix is ​​significantly improved, and the metallurgical interface combination between ZTA ceramics and high chromium cast iron matrix is ​​achieved.

Benefits of technology

It significantly improves the overall wear resistance of ZTA ceramics to enhance high-chromium cast iron matrix composite materials, and promotes its industrial production and large-scale engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229693160000101
    Figure BDA0005229693160000101
  • Figure HDA0005229693200000011
    Figure HDA0005229693200000011
  • Figure HDA0005229693200000012
    Figure HDA0005229693200000012
Patent Text Reader

Abstract

The invention discloses a high-wear-resistance FeZr-ZTA micro powder coated ZTA ceramic reinforced high-chromium cast iron-based composite material as well as preparation and application thereof. The preparation method comprises the following steps: firstly, ball-milling Zr-Fe powder and ZTA micro powder into a mixed powder binder, wrapping the mixed powder binder on the surfaces of ZTA particles, pre-sintering at 1000-1200 DEG C, then mixing pre-coated ZTA particles with the binder to coat the surfaces of the pre-coated ZTA particles, and carrying out pressureless sintering to obtain a ZTA ceramic preform; and finally, the ZTA ceramic particle reinforced high-chromium cast iron composite material is obtained through a casting infiltration method. Through the bridge action of the FeZr-ZTA micro powder coating layer, a metallurgical bonding interface can be formed between ZTA and a high-chromium cast iron matrix, so that the prepared ZTA ceramic particle reinforced high-chromium cast iron composite material has excellent three-body wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material processing, and specifically relates to a high-wear-resistant FeZr-ZTA micropowder-coated ZTA ceramic-reinforced high-chromium cast iron-based composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern industry, the consumption of wear-resistant metal materials is increasing day by day, but traditional wear-resistant metal materials are difficult to meet the requirements of complex working conditions, and it is urgent to develop new wear-resistant metal materials with excellent wear resistance. Ceramic reinforced high-chromium cast iron-based composites have both the high hardness, high specific strength, high wear resistance, and high thermal stability of ceramics and the good toughness, plasticity and impact resistance of metals. As wear-resistant materials, the application prospects are very broad, among which zirconia toughened alumina (ZTA) reinforced high-chromium cast iron-based composites have attracted much attention.

[0003] The addition of ceramic particles to ceramic particle reinforced high chromium cast iron matrix composites is mainly used to improve the wear resistance of high chromium cast iron materials. During service, the wear principle is that the high chromium cast iron body supports and fixes the ceramic particles, and as the high chromium cast iron matrix wears, the ceramic particles stand out as the main anti-wear phase, and the entire ceramic particles form a skeleton to reduce further wear of the high chromium cast iron body material. However, the wettability of ZTA ceramic particles and high chromium cast iron bodies is very poor, so how to improve the interface bonding strength between ceramic particles and high chromium cast iron to achieve metallurgical bonding is the key prerequisite for the further widespread application of this composite material.

[0004] The bonding mode of the interface between ceramic particles and metal directly determines the strength of the interface formed and the wear resistance of the composite material. The interface bonding modes are: physical bonding, mechanical bonding, metallurgical bonding and mixed bonding, among which the interface strength of metallurgical bonding is the strongest. However, the interface bonding mode of ceramic particles reinforced high-chromium cast iron composite materials at home and abroad is mainly mechanical bonding, and metallurgical bonding has not yet been achieved. This is mainly due to the completely different chemical properties, thermal expansion coefficients and other characteristics of ceramics and high-chromium cast iron, and the poor wettability of the two, which leads to the poor bonding of the interface between ceramic particles and high-chromium cast iron. Therefore, how to improve the surface activity of ZTA ceramics and improve its wettability with the high-chromium cast iron matrix to achieve metallurgical bonding and achieve excellent wear resistance has always been the focus of research. The present invention pioneered the development of FeZr-ZTA micropowder coated ZTA ceramic particle surface activation treatment technology, which significantly improved the interface wettability of ceramic particles and high-chromium cast iron matrix, achieved the metallurgical interface bonding of ZTA ceramics and high-chromium cast iron matrix, and the wear resistance of the prepared composite material was significantly improved. The results of the present invention can effectively promote the industrial production and large-scale engineering application of highly wear-resistant ZTA reinforced high-chromium cast iron-based composite materials. It is also suitable for the development of other iron-based composite materials such as alloy steel and high manganese steel, and has very important theoretical and engineering application value. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for activating the surface of a porous preform of a ZTA ceramic coated with FeZr-ZTA powder.

[0006] Another object of the present invention is to provide a FeZr-ZTA micropowder-coated ZTA ceramic porous preform and application thereof.

[0007] Another object of the present invention is to provide a method for preparing a highly wear-resistant FeZr-ZTA micropowder-coated ZTA ceramic reinforced high chromium cast iron-based composite material, which can achieve metallurgical bonding between ZTA ceramic particles and the high chromium cast iron matrix, thereby significantly improving the overall wear resistance of the ZTA ceramic reinforced high chromium cast iron-based composite material.

[0008] Another object of the present invention is to provide a highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high chromium cast iron-based composite material and its application.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for activating the surface of a porous preform of a ZTA ceramic coated with FeZr-ZTA micropowder comprises the following steps:

[0011] (1) mixing Zr-Fe powder and ZTA powder by ball milling to obtain FeZr-ZTA mixed powder;

[0012] (2) FeZr-ZTA mixed powder and anhydrous ethanol are mixed to obtain a slurry, and then ZTA particles are immersed in the slurry to completely and evenly coat the surface of the ZTA particles, the ZTA particles are taken out and dried, and then pre-sintered at 800-950° C. to obtain pre-coated ZTA particles;

[0013] (3) The pre-coated ZTA particles are sintered at 1150-1550° C. to obtain a FeZr-ZTA micropowder-coated ZTA ceramic porous preform.

[0014] Preferably, the particle size of the Zr-Fe powder in step (1) is ≤200 mesh.

[0015] Preferably, the mass percentage of Zr in the Zr-Fe powder in step (1) is 10-60%.

[0016] Preferably, the particle size of the ZTA powder in step (1) is 3 to 8 microns.

[0017] Preferably, the weight ratio of the Zr-Fe powder to the ZTA powder in step (1) is 3-6:2-5.

[0018] Preferably, the ball milling in step (1) is mechanical ball milling, the ball diameter of the grinding balls is 5 to 10 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 10:1, the rotation speed is 300 to 450 r / min, and the ball milling time is 360 to 480 min.

[0019] Preferably, in step (2), by weight percentage, the FeZr-ZTA mixed powder accounts for 20-27 wt.%, the anhydrous ethanol accounts for 20-25 wt.%, and the remainder is ZTA particles.

[0020] Preferably, the average particle size of the ZTA particles in step (2) is 8 to 10 meshes.

[0021] Preferably, the drying in step (2) refers to drying under vacuum conditions at 50-100° C. for 3-4 hours, in order to remove the anhydrous ethanol in the particles.

[0022] Preferably, the pre-sintering time in step (2) is 45 to 60 minutes.

[0023] Preferably, the ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

[0024] Preferably, the pressureless sintering time in step (3) is 120 to 180 minutes.

[0025] The invention provides a FeZr-ZTA micropowder-coated ZTA ceramic porous preform, which is obtained by the surface activation method.

[0026] The present invention provides the use of the FeZr-ZTA micropowder-coated ZTA ceramic porous preform in reinforcing metal or metal alloy-based composite materials.

[0027] Preferably, the steps of applying include:

[0028] The FeZr-ZTA micropowder-coated ZTA ceramic porous preform is fixed in a casting cavity, and a metal or metal alloy melt is cast into the cavity to obtain a ZTA ceramic particle-reinforced metal or metal alloy matrix composite material.

[0029] Preferably, the metal alloy is an iron-based alloy, more preferably high-chromium cast iron.

[0030] The present invention provides a method for preparing a high-wear-resistant FeZr-ZTA micropowder-coated ZTA ceramic-reinforced high-chromium cast iron-based composite material, comprising the following steps:

[0031] (1) mixing Zr-Fe powder and ZTA powder by ball milling to obtain FeZr-ZTA mixed powder;

[0032] (2) FeZr-ZTA mixed powder and anhydrous ethanol are mixed to obtain a slurry, and then ZTA particles are immersed in the slurry to completely and evenly coat the surface of the ZTA particles, the ZTA particles are taken out and dried, and then pre-sintered at 800-950° C. to obtain pre-coated ZTA particles;

[0033] (3) pressurelessly sintering the pre-coated ZTA particles at 1150-1550° C. to obtain a FeZr-ZTA micropowder-coated ZTA ceramic porous preform;

[0034] (4) A FeZr-ZTA micropowder-coated ZTA ceramic porous preform is fixed in a casting cavity, and high-temperature high-chromium cast iron liquid is cast into the cavity to obtain a composite material with metallurgical bonding at the interface between the ZTA ceramic and the high-chromium cast iron matrix.

[0035] Preferably, the particle size of the Zr-Fe powder in step (1) is ≤200 mesh.

[0036] Preferably, the mass percentage of Zr in the Zr-Fe powder in step (1) is 10-60%.

[0037] Preferably, the particle size of the ZTA powder in step (1) is 3 to 8 microns.

[0038] Preferably, the weight ratio of the Zr-Fe powder to the ZTA powder in step (1) is 3-6:2-5.

[0039] Preferably, the ball milling in step (1) is mechanical ball milling, the ball diameter of the grinding balls is 5 to 10 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 10:1, the rotation speed is 300 to 450 r / min, and the ball milling time is 360 to 480 min.

[0040] Preferably, in step (2), by weight percentage, the FeZr-ZTA mixed powder accounts for 20-27 wt.%, the anhydrous ethanol accounts for 20-25 wt.%, and the remainder is ZTA particles.

[0041] Preferably, the particle size of the ZTA particles in step (2) is 8 to 10 meshes.

[0042] Preferably, the drying in step (2) refers to drying under vacuum conditions at 50-100° C. for 3-4 hours, in order to remove the anhydrous ethanol in the particles.

[0043] Preferably, the pre-sintering time in step (2) is 45 to 60 minutes.

[0044] Preferably, the ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

[0045] Preferably, the pressureless sintering time in step (3) is 120 to 180 minutes.

[0046] Preferably, the casting temperature of the high chromium cast iron in step (4) is 1350±15°C to 1450±20°C; the furnace outlet temperature of the high chromium cast iron is 1500±20°C.

[0047] Preferably, slag removal and deoxidation treatment may be performed before casting in step (4).

[0048] The above-mentioned method for preparing a highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high chromium cast iron matrix composite material is a method for achieving metallurgical bonding at the interface between ZTA ceramic particles and a high chromium cast iron matrix.

[0049] The invention provides a high-wear-resistant FeZr-ZTA micropowder-coated ZTA ceramic-reinforced high-chromium cast iron-based composite material prepared by the preparation method.

[0050] The present invention provides application of the above-mentioned highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high-chromium cast iron-based composite material in components such as mining machinery linings.

[0051] The method of the present invention uses FeZr-ZTA powder to modify the surface of ZTA ceramics, which can effectively improve the interface bonding characteristics between ceramics and metals, improve the wettability of the ceramic surface to liquid metal, and achieve metallurgical bonding between the molten metal and the ceramics.

[0052] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0053] (1) As a surfactant for ceramic particles, FeZr-ZTA powder can effectively improve the interfacial bonding properties between ceramics and metals, improve the wettability of the ceramic surface to liquid metal, and enhance the metallurgical bonding strength between the liquid metal and ceramics.

[0054] (2) The raw materials used in the present invention are all directly sold on the market, which reduces the cost and is conducive to industrial large-scale production. The preform is not subjected to a pressing treatment before sintering, but is left to stand naturally. It is precisely this treatment that makes the preform appear loose and porous, which is conducive to the filling of high-chromium cast iron liquid between ZTA particles.

[0055] (3) This technology has high universality and simple equipment requirements, and can be applied to the production and preparation of other iron-based composite materials (such as high manganese steel and alloy steel matrices). BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a physical picture of the preform prepared in Example 1;

[0057] Figure 2 The SEM scanning image of the composite interface of the composite material prepared in Example 1 and the EDS energy spectrum line scanning spectrum corresponding to the composite interface;

[0058] Figure 3 This is a high-magnification SEM image of the interface of the composite material prepared in Example 1. DETAILED DESCRIPTION

[0059] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0060] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0061] Example 1

[0062] (1) Zr powder and Fe powder with a purity of about 99.99% and a particle size not exceeding 200 mesh (the mass percentage of Zr in the Zr-Fe powder is 60%) and ZTA powder with a particle size of 3 μm are mixed in a weight ratio of Zr-Fe:ZTA 3:2, and mechanical ball milling is performed. The main mechanical alloying parameters are as follows: grinding ball diameter: 10 mm, ball-to-material ratio 5:1, ball milling speed 400 r / min, ball milling time 480 min, to obtain FeZr-ZTA mixed powder.

[0063] In order to prevent the surface area of ​​the mixed powder from increasing after ball milling and reacting easily with oxygen in the air, the mixed powder is carried out in an inert gas (nitrogen) environment during the entire mechanical ball milling mixing process.

[0064] (2) Pour the FeZr-ZTA mixed powder (20 wt.%) obtained by ball milling in step (1) into a container, add 20 wt.% of anhydrous ethanol, and stir continuously until a thick slurry is formed, then immerse 60 wt.% ZTA particles (average particle size 8 mesh) into the slurry, and stir continuously to coat the ZTA particles with the slurry, then remove the ZTA particles and place them in a vacuum drying oven for 4 hours. Finally, place the dried ZTA particles in a furnace and heat to 800°C, pre-sinter for 60 minutes, cool the furnace to room temperature and take them out to obtain pre-coated ZTA particles. The entire sintering process is carried out under a nitrogen protective atmosphere.

[0065] (3) The ZTA particles coated in step (2) are placed in a corundum mold with a height of 60 mm and a diameter of 50 mm, and sintered at 1150° C. for 180 min. After demolding, the desired ZTA ceramic preform is obtained. To facilitate demolding, a layer of graphite paper with a thickness of about 0.5 mm can be placed inside the mold. The entire sintering process is carried out under the protection of inert gas (nitrogen).

[0066] (4) ZTA / HCCI composite materials were prepared by conventional sand casting. The prepared ZTA ceramic preform was fixed in the middle of the mold cavity with a thick iron wire. High chromium cast iron (HCCI) was used as the casting melt. The temperature of the molten iron out of the furnace was controlled at 1500±20℃, and the casting temperature was controlled at 1450±20℃. Deslagging and deoxidation treatment were performed before casting.

[0067] The macroscopic image of the ZTA ceramic preform prepared in Example 1 is as follows: Figure 1 As shown; Figure 2The SEM scan of the ceramic particle reinforced high chromium cast iron composite material prepared in Example 1 and the EDS energy spectrum line scanning spectrum corresponding to the composite interface. The formation of the transition layer can be clearly seen from the figure. The results of the EDS energy spectrum line scanning spectrum show that the Cr and O elements continuously transition and diffuse from the high chromium cast iron matrix on the left to the right. The content of these elements at the interface does not change abruptly, but shows a gradual trend, and a component diffusion phenomenon occurs; it can be seen from the figure that a metallurgical bonding interface is formed between ZTA and the high chromium cast iron matrix, and the interface bonding is good. After three-body abrasive wear test, the test conditions are: the abrasive is 6# quartz sand, the main speed of the wear testing machine is 30r / min, the single wear time is 30min (6 times in total, a total of 180min), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The average value is taken as the final result. The wear rate of the ZTA / HCCI composite material is only 0.53mm 3 ·min -1 .

[0068] Example 2

[0069] (1) Zr powder and Fe powder with a purity of about 99.99% and a particle size not exceeding 200 mesh (the mass percentage of Zr in the Zr-Fe powder is 10%) and ZTA powder with a particle size of 8 μm are mixed in a weight ratio of Zr-Fe:ZTA 6:5, and mechanical ball milling is performed. The main mechanical alloying parameters are as follows: grinding ball diameter: 5 mm, ball-to-material ratio 10:1, ball milling speed 300 r / min, ball milling time 360 ​​min, and FeZr-ZTA mixed powder is obtained.

[0070] In order to prevent the surface area of ​​the mixed powder from increasing after ball milling and reacting easily with oxygen in the air, the mixed powder is carried out in an inert gas (nitrogen) environment during the entire mechanical ball milling mixing process.

[0071] (2) Pour the FeZr-ZTA mixed powder (27 wt.%) obtained by ball milling in step (1) into a container, add 25 wt.% anhydrous ethanol, and stir continuously until a thick slurry is formed, then immerse 48 wt.% ZTA particles (average particle size of 10 mesh) into the slurry, and stir continuously to coat the ZTA particles with the slurry, then remove the ZTA particles and place them in a vacuum drying oven for 4 hours. Finally, place the dried ZTA particles in a furnace and heat to 950°C, pre-sinter for 60 minutes, cool the furnace to room temperature and take out to obtain pre-coated ZTA particles. The entire sintering process is carried out under a nitrogen protective atmosphere.

[0072] (3) The ZTA particles coated in step (2) are placed in a corundum mold with a height of 60 mm and a diameter of 50 mm, and pressurelessly sintered at 1550° C. for 120 min. After demolding, the desired ZTA ceramic preform is obtained. To facilitate demolding, a layer of graphite paper with a thickness of about 0.5 mm can be placed inside the mold. The entire sintering process is carried out under the protection of inert gas (nitrogen).

[0073] (4) ZTA / HCCI composite materials were prepared by conventional sand casting. The prepared ZTA ceramic preform was fixed in the middle of the mold cavity with a thick iron wire. High chromium cast iron (HCCI) was used as the casting melt. The temperature of the molten iron out of the furnace was controlled at 1500±20℃, and the casting temperature was controlled at 1350±15℃. Deslagging and deoxidation treatment were performed before casting.

[0074] Figure 3 This is a SEM scan of the ceramic particle reinforced high chromium cast iron composite material prepared in Example 2. It can be clearly seen from the figure that a transition metallurgical bonding interface is formed between the ZTA ceramic particles and the high chromium cast iron matrix, and the interface bonding is good. After three-body abrasive wear test, the test conditions are: the abrasive is 6# quartz sand, the main speed of the wear testing machine is 30r / min, the single wear time is 30min (6 times in total, a total of 180min), the load is 30N, and the radius of the circular rail is 180mm. Each sample was subjected to three wear tests, and the average value was taken as the final result. The wear rate of the ZTA / HCCI composite material is only 0.72mm 3 ·min -1 .

[0075] Example 3

[0076] (1) Zr powder and Fe powder with a purity of about 99.99% and a particle size not exceeding 200 mesh (the mass percentage of Zr in the Zr-Fe powder is 30%) and ZTA powder with a particle size of 5 μm are mixed in a weight ratio of Zr-Fe:ZTA 4:5, and mechanical ball milling is performed. The main mechanical alloying parameters are: grinding ball diameter: 5 mm, ball-to-material ratio 10:1, ball milling speed 300 r / min, ball milling time 360 ​​min, and FeZr-ZTA mixed powder is obtained.

[0077] In order to prevent the surface area of ​​the mixed powder from increasing after ball milling and reacting easily with oxygen in the air, the mixed powder is carried out in an inert gas (nitrogen) environment during the entire mechanical ball milling mixing process.

[0078] (2) Pour the FeZr-ZTA mixed powder (25wt.%) obtained by ball milling in step (1) into a container, add 20wt.% anhydrous ethanol, and stir continuously until a thick slurry is formed, then immerse 45wt.% ZTA particles (average particle size of 8 mesh) into the slurry, and stir continuously to coat the ZTA particles with the slurry, then remove the ZTA particles and place them in a vacuum drying oven for 4h. Finally, place the dried ZTA particles in a furnace and heat to 850°C, pre-sinter for 45min, cool the furnace to room temperature and take them out to obtain pre-coated ZTA particles. The entire sintering process is carried out under a nitrogen protective atmosphere.

[0079] (3) The coated ZTA particles in step (2) are placed in a corundum mold with a height of 60 mm and a diameter of 50 mm, and pressurelessly sintered at 1450° C. for 120 min. After demolding, the desired ZTA ceramic preform is obtained. To facilitate demolding, a layer of graphite paper with a thickness of about 0.5 mm can be placed inside the mold. The entire sintering process is carried out under the protection of inert gas (nitrogen).

[0080] (4) ZTA / HCCI composite materials were prepared by conventional sand casting. The prepared ZTA ceramic preform was fixed in the middle of the mold cavity with a thick iron wire. High chromium cast iron (HCCI) was used as the casting melt. The temperature of the molten iron out of the furnace was controlled at 1500±20℃, and the casting temperature was controlled at 1400±15℃. Deslagging and deoxidation treatment were performed before casting.

[0081] After three-body abrasive wear test, the test conditions are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (6 times in total, a total of 180min), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The average value is taken as the final result. The wear rate of the ZTA / HCCI composite material is only 0.65mm 3 ·min -1 .

[0082] Comparative Example 1

[0083] (1) After cleaning the untreated ZTA particles with alcohol, place them in a vacuum drying oven for drying. Weigh an appropriate amount of ZTA particles, and fully stir and evenly mix the ZTA and water glass binder (accounting for about 10% of the mass of ZTA). Subsequently, press the mixed ZTA particles into a mold, and then place the preform together with the mold into a drying oven at 70°C for 5 hours. After drying, take out the preform to obtain a formed ZTA ceramic preform. The mold size used is 40mm×60mm, and a layer of graphite paper can be placed inside the mold to facilitate demolding.

[0084] (3) ZTA / HCCI composite materials were prepared by conventional sand casting. The prepared ZTA ceramic preform was fixed in the middle of the mold cavity with a thick iron wire. High chromium cast iron (HCCI) was used as the casting melt. The temperature of the molten iron out of the furnace was controlled at 1350±15℃, and the casting temperature was controlled at 1450±20℃. Deslagging and deoxidation treatment were performed before casting.

[0085] Due to the introduction of water glass, a transition layer can be formed between high chromium cast iron and ZTA ceramic particles, but there are many impurities such as non-metallic salts, and the interface bonding strength is low.

[0086] After three-body abrasive wear test, the test conditions are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (6 times in total, a total of 180min), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests, and the average value is taken as the final result. The wear rate of the ZTA / HCCI composite material is 0.95mm 3 ·min -1 .

[0087] Table 1 Three-body wear rate of the composite materials prepared in Examples 1-3 and Comparative Example 1

[0088]

[0089] It can be seen from Table 1 that the wear resistance of the composite materials obtained in Examples 1-3 has certain differences, but they are all obviously superior to the wear resistance of the composite material prepared in Comparative Example 1.

[0090] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for activating the surface of a porous preform of ZTA ceramics coated with FeZr-ZTA powder, characterized in that: The following steps are involved: (1) mixing Zr-Fe powder and ZTA powder by ball milling to obtain FeZr-ZTA mixed powder; (2) FeZr-ZTA mixed powder and anhydrous ethanol are mixed to obtain a slurry, and then ZTA particles are immersed in the slurry to completely and evenly coat the surface of the ZTA particles, the ZTA particles are taken out and dried, and then pre-sintered at 800-950° C. to obtain pre-coated ZTA particles; (3) The pre-coated ZTA particles are pressurelessly sintered at 1150-1550° C. to obtain a FeZr-ZTA micropowder-coated ZTA ceramic porous preform.

2. The method according to claim 1, characterized in that: The mass percentage of Zr in the Zr-Fe powder of step (1) is 10-60%; The weight ratio of the Zr-Fe powder to the ZTA powder in step (1) is 3-6:2-5; In step (2), by weight percentage, the FeZr-ZTA mixed powder accounts for 20-27 wt.%, the anhydrous ethanol accounts for 20-25 wt.%, and the balance is ZTA particles.

3. The method according to claim 1 or 2, characterized in that: The particle size of the Zr-Fe alloy powder in step (1) is ≤200 mesh; The particle size of the ZTA powder in step (1) is 3 to 8 microns; The average particle size of the ZTA particles in step (2) is 8 to 10 meshes; The ball milling in step (1) is a mechanical ball milling, the ball diameter of the grinding balls is 5 to 10 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 10:1, the rotation speed is 300 to 450 r / min, and the ball milling time is 360 to 480 min.

4. The method according to claim 1 or 2, characterized in that: The pre-sintering time in step (2) is 45 to 60 minutes; The time of the pressureless sintering in step (3) is 120 to 180 minutes.

5. The method according to claim 1 or 2, characterized in that: The drying in steps (2) and (3) refers to drying under vacuum conditions at 50 to 100° C. for 3 to 4 hours; The ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

6. A FeZr-ZTA micropowder-coated ZTA ceramic porous preform obtained by the method according to any one of claims 1 to 5.

7. Use of a FeZr-ZTA micropowder coated ZTA ceramic porous preform as claimed in claim 6 in reinforcing metal or metal alloy matrix composite materials, characterized in that: Achieve metallurgical bonding at the interface between ZTA ceramics and metal or metal alloy substrates.

8. A method for preparing a highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high chromium cast iron based composite material, characterized in that: The following steps are involved: The FeZr-ZTA powder-coated ZTA ceramic porous preform of claim 6 is fixed in a casting cavity, and a high-chromium cast iron melt is cast into the cavity to obtain a composite material with metallurgical bonding at the interface between the ZTA ceramic and the high-chromium cast iron matrix; The casting temperature of the high chromium cast iron melt is 1350±15°C to 1450±20°C; the furnace outlet temperature of the high chromium cast iron melt is 1500±20°C.

9. A highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high chromium cast iron based composite material obtained by the preparation method of claim 8.

10. Use of the highly wear-resistant FeZr-ZTA micropowder coated ZTA ceramic reinforced high chromium cast iron based composite material as described in claim 9 in mining machinery lining components.

Citation Information

Patent Citations

  • A porous ZTA ceramic prefabricated body covered with Cu-Ti alloy micropowder and preparation and application thereof

    CN109020603A

  • Preparation method for surface treatment ZTA particle enhanced steel-based composite grinding roller

    CN110935864A

  • Method for preparing ZTA ceramic particle reinforced high-chromium cast iron-based wear-resistant composite material

    CN113560540A

  • Micro-nano-scale ceramic particle reinforced high-chromium cast iron-based composite material as well as preparation method and application thereof

    CN119177391A

Cited By

  • Anti-adhesion asphalt drying device

    CN120593478A